In situ denitrification of nitrate rich groundwater in Marydale, Northern Cape - Israel (Clarke), Sumaya (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Soil Science))--University of Stellenbosch, 2007.